The biomimetic detection of progesterone by novel bifunctional group monomer based molecularly imprinted polymers prepared in UV light. (20th April 2020) - Nawaz, Tehseen; Ahmad, Muhammad; Yu, Jieying; Wang, Shiqi; Wei, Tianxin
Abstract : A novel itaconic acid based progesterone imprinted biosensor was prepared via a reversible addition chain transfer mechanism and surface plasmon resonance. Abstract : Novel bifunctional group monomer itaconic acid (IA) based molecularly imprinted polymers (MIPs) were successfully prepared with hydrogen bonding interactions by applying a facile combination of a reversible addition chain transfer mechanism (RAFT) and surface plasmon resonance (SPR). UV photo-polymerization in synergy with 2-methyl-2-[(dodecylsulfanylthiocarbonyl)sulfanyl]propanoic acid (TTCA) as a chain transfer reagent was employed for MIP film synthesis on an SPR sensor chip for the detection of progesterone using ethylene glycol dimethacrylate (EGDMA) as a cross linker. In addition, the ratio of template to bifunctional group monomer to cross linker was optimized (1 : 2 : 12) by real-time SPR monitoring. The modified surface of the biosensor was characterized by contact angle measurements, frontier transfer infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The resulting itaconic acid based MIP (IA based MIP) biosensor showed a high adsorption capacity and excellent selectivity in comparison to other analogues and non-imprinted polymer (NIP) film. Through 8 adsorption–desorption cycles, the high recoverability of IA based MIP film was confirmed. These features suggested that IA based MIPs are ideal candidates for biosensor use owing to the bifunctionality of the monomer. Consequently, within the concentration range of 1 × 10 −18 to 1 × 10 −8 mol L −1, the coupling angle change of SPR versus the negative logarithm of concentration showed excellent linearity: R 2 = 0.99. Based on a linear equation, IA based MIPs showed excellent values for the limit of detection (LOD) and limit of quantification (LOQ), i.e. 0.28 × 10 −19 mol L −1 and 0.92 × 10 −19 mol L −1, respectively. Furthermore, the influence of the matrix on the biosensor was successfully analyzed in real samples with satisfactory outcomes, displaying identical behavior to ideal samples. Hence, IA based MIPs in combination with an SPR sensor chip demonstrated potential applications for rapid and highly effective sensing even in complicated matrices.